Chemokines and activated macrophages in HIV gp120-induced neuronal apoptosis - Kaul, Marcus (The National Academy of Sciences, 1999)
HIV-1 glycoprotein gp120 induces injury and apoptosis in rodent and human neurons in vitro and in vivo and is therefore thought to contribute to HIV-associated dementia. In addition to CD4, different gp120 isolates bind to the α- or β-chemokine receptors CXCR4 and CCR5, respectively. These and other chemokine receptors are on brain macrophages/microglia, astrocytes, and neurons. Thus, apoptosis could occur via direct interaction of gp120 with neurons, indirectly via stimulation of glia to release neurotoxic factors, or via both pathways. Here we show in rat cerebrocortical cultures that recapitulate the type and proportion of cells normally found in brain, i.e., neurons, astrocytes, and macrophages/microglia, that the β-chemokines RANTES (regulated on activation, normal T cell expressed and secreted) and macrophage inflammatory protein (MIP-1β) protect neurons from gp120(SF2)-induced apoptosis. The gp120(SF2) isolate prefers binding to CXCR4 receptors, similar to the physiological α-chemokine ligands, stromal cell-derived factor (SDF)-1α/β. SDF-1α/β failed to prevent gp120(SF2) neurotoxicity, and in fact also induced neuronal apoptosis. We could completely abrogate gp120(SF2)-induced neuronal apoptosis with the tripeptide TKP, which inhibits activation of macrophages/microglia. In contrast, TKP or depletion of macrophages/microglia did not prevent SDF-1 neurotoxicity. Inhibition of p38 mitogen-activated protein kinase ameliorated both gp120(SF2)- and SDF-1-induced neuronal apoptosis. Taken together, these results suggest that gp120(SF2) and SDF-1 differ in the cell type on which they stimulate CXCR4 to induce neuronal apoptosis, but both ligands use the p38 mitogen-activated protein kinase pathway for death signaling. Moreover, gp120(SF2)-induced neuronal apoptosis depends predominantly on an indirect pathway via activation of chemokine receptors on macrophages/microglia, whereas SDF-1 may act directly on neurons or astrocytes.